The effect of financial ratios and company size on dividend policy - Riri Nerviana (Universitas Hayam Wuruk Perbanas, 2015)
The purpose of this research is to find out whether there is an effect of financial ratios on dividend policy, which is proxied by Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Return on Equity (ROE), Growth of Sales (GS), and Price Earning Ratio (PER), and the Company Size on the Dividend Policy of the company, which is proxied by Dividend Payout Ratio (DPR). The population of this study is manufacturing companies listed in Indonesia Stock Exchange from 2009 to 2013. This study uses purposive sampling method and its subject of 29 companies of the 145 companies that have been observed. The analytical techniques used in this research consist of descriptive statistics test, normality test, multiple linear regressions analysis, and hypothesis test comprising an analysis of the coefficient of determination (R2), model test research (statistical tests F), and a partial test (statistics test of t). The results indicate that only Debt to Equity Ratio (DER), Return on Equity (ROE), and Price Earnings Ratio (PER) that have significant effect on dividend policy.